Addressing Ethical Challenges Related to Community and Patient Engagement in Health Research - Emily Cordeaux; Natasha Yasmin Sheikhan; Rhonda Boateng (Canadian Journal of Bioethics, 2024)
In this post-workshop summary, we describe three ethical challenges related to engaging people with lived experience as partners in health research. We share learnings and reflective prompts from our workshop delivered as part of the Canadian Bioethics Society Workshop and Community Forum held in May 2023.